THE POTENTIAL USE OF ANTI-NUTRITIONAL COMPOUNDS OF GADUNG TUBERS AS BIOPESTICIDES - Riva Ismawati; Feni Nurhidayanti; Theresya Amelya Dhewi; Cucun Yuningsih (JURNAL PENA SAINS, 2021)
The use of gadung (Discorea hispida dennst.) tubers as food source is not seen as an attractive option due to dioscorine and cyanide anti-nutritional compounds contained therein. The presence of dioscorine and cyanide compounds makes gadung tubers known as poisonous food. Although the community has known its poisonous nature, the use of gadung tubers as natural pesticides (biopesticides) is not commonly known by the community. Using gadung tubers as biopesticides provides solution to unanswered problems caused by chemical pesticides. This article seeks to describe the potential use of anti-nutritional compounds of gadung tubers as biopesticides based on literature reviews. Various literature related to anti-nutritional compounds contained in gadung tubers and their use as biopesticides have been analyzed in depth. The literature review results show that dioscorine and cyanide anti-nutritional compounds are toxic and can be used as biopesticides. The effectiveness of gadung tubers on various agricultural pests depends entirely on the concentration of gadung tubers used. The use of gadung tubers as biopesticides is needed to increase and maintain the productivity of agricultural land in addition to preserving natural resources.